Open source seismic visualization package on OpenNebula cloud management system - Zain, F.M. (Institute of Electrical and Electronics Engineers Inc., 2016)
Currently, the exploration of oil and gas have become more complex due to the oil depletion. The increasing difficulties in discovering new hydrocarbon reservoirs using existing technologies have caused an exceptional rise in the cost and risk to discover hydrocarbons. Seismic interpretation is one of the main element in oil exploration. Seismic interpretation software is vital to assist geophysicists to find hydrocarbons trap. However, specialized commercial seismic visualization package is highly priced. Hence, open source seismic visualization package is introduced as an alternative to minimize the cost in oil exploration. The goal of this research is to demonstrate through comparative study of computing functionalities between two different types of open source seismic visualization packages in order to find a preferable one to integrate in cloud infrastructure, OpenNebula cloud. This paper addresses how the author chooses OpendTect over ParaViewGeo as the preferable open source seismic visualization packages by comparing the functionality of the software packages. In addition, a research study on OpenNebula also has been done to understand the working principle of this cloud management system. Furthermore, an experiment has been conducted to test whether or not the preferable open source seismic visualization package is able to be integrated correctly in OpenNebula cloud with high scalability and good performance. Â© 2015 IEEE.